The Social Cost of Carbon with Intragenerational Inequality under Economic Uncertainty - Rick van der Ploeg; Johannes Emmerling; Ben Groom (Center for Economic Studies and ifo Institute (CESifo), 2022)
A formula is derived for the social cost of carbon (SCC) that takes account of intragenerational income inequality and its evolution with economic growth. The social discount rate (SDR) should be adjusted to account for intragenerational and intergenerational inequality aversion and for risk aversion. If growth increases (reduces) intra-generational inequality, the SDR is lower (higher) and the SCC higher (lower) than along an inequality-neutral growth path, especially if intra-generational and intergenerational inequality aversion are higher. The same qualitative result is shown for two welfare specifications, one with a representative agent with equally distributed equivalent (EDE) income and the other considers individuals separately across the income distribution. The latter specification causes an additional impact of income inequality on the SDR and SCC because individuals are compared both within and between time periods. Our preferred EDE calibration to a scenario in which global intragenerational inequality declines over time, leads to a SCC in 2020 of 70/tCO2 compared to a value of 85/tCO2 without the effect of inequality.
Keywords: C61; D31; D62; D81; G12; H23; Q54; 330; social discount rate; social cost of carbon; intra- and intergenerational inequality aversion; risk aversion; inequality; growth; uncertainty